Chimeric Negative Regulation of p14ARF and TBX1 by a t(9;22) Translocation Associated with Melanoma, Deafness, and DNA Repair Deficiency. Issue 9 (3rd June 2013) - Tan, Xiaohui; Anzick, Sarah L.; Khan, Sikandar G.; Ueda, Takahiro; Stone, Gary; DiGiovanna, John J.; Tamura, Deborah; Wattendorf, Daniel; Busch, David; Brewer, Carmen C.; Zalewski, Christopher; Butman, John A.; et al.
<x xml:space="preserve">Abstract</x> We studied a patient with melanoma, DNA repair deficiency, and deafness due to malformed inner ears who had a novel balanced t(9;22) translocation. Sequencing this break region served as a "Rosetta stone" permitting identification of a new gene, FAM230A, within a gap region on chromosome 22. The chimeric p14ARF‐FAM230A gene appears to play an important dominant negative regulatory role in melanoma induction and ear development in this patient. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>